Analisis Kandungan Nutrisi Pada Produk Nugget Gonad Landak Laut Tripneustes gratilla (Linnaeus 1758) - Yeni Savitri Andi Lawi; Kariyanti Kariyanti; Ernawati Ernawati; Nur Hasanah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2020)
The aim of this research is to identify the proximate / nutritional content of Nugoda products from processed fresh sea urchin gonad Tripneustes gratilla. The research will last for sevent months with 36 experimental designs, samples taken from the Barrang Lompo Islands area of ​​Makassar. Fresh gonads obtained were then made into a product (NUGODA) Tripneustes gratilla after which analyzed the nutritional content contained in the product (proximate) by the AOAC method. The results of this study get the value of the nutrient content by treatment (A1, A2, A3, A4) where the gonad ratio is as much (0 g, 150 g, 200 g, 250 g). The best results obtained nutrient content in need A4 with Added 250 g fresh gonad where the average protein content produced 8.51%, fat content 5.63%, ash 2.13% and water content 60.37% where the results obtained have met the Fish Nugget Standard (SNI 7758: 2013).